iHadir: Web-Based Student Attendance System Using RFID Technology - Mohamed Ali, Mohd Hatta; Mohamad Haikal Hussin; Kamisan, Aiman Syafiq; Shabudin, Muhammad Hafez Nadzrin; Abdul Halim Omar (Multidisciplinary Applied Research and Innovation, 2021)
The Web-Based Student Attendance System Using Rfid Technology is a system that we developed to record student attendance using Radio-Frequency Identification (RFID) equipment in schools. The RFID is made up of several components like a small transponder radio, radio receiver and transmitter. When it triggered, the electromagnetic interrogation pulse from the nearby RFID tags will transmits digital data from the RFID tags and back to the reader. The data that were transmitted can be used as identification or record. It integrates the principles of the web base system by using devices such as RFID cards and RFID card readers to record student attendance. This system is designed to facilitate teachers' ability to review and store school attendance data. These data are stored in a database, which is designed specifically to store student data, where it integrates attendance data for each student on a daily basis using RFID techniques. It’s difficult for the teacher and the class to build their skills and progress if a large number of students are frequently absent. Unlike other system, the RFID tags were developed to allowed the teacher easily track down the students throughout when they still school. The data also kept well in school database. Moreover, the data allows the teacher to find information of their students even thought they had left the school. This system also have a huge potential for commercialization.